2021
DOI: 10.1080/09540105.2021.1940877
|View full text |Cite
|
Sign up to set email alerts
|

Multi-wavelength fluorescence polarization immunoassays for simultaneous detection of amantadine and ribavirin in chicken and human serum

Abstract: In this study, a homologous multi-wavelength fluorescence polarization immunoassays (MWFPIA) for rapid determination of amantadine (AMD) and ribavirin (RVB) simultaneously was established. The MWFPIA could quantify AMD and RVB concentration simultaneously in 1 min. After optimisation, longwavelength tracers AEDA-AF647 with monoclonal antibody (Mab) 1A12 and RVB-CP-EDF with polyclonal antibody (Pab) G412 were chosen for the development of MWFPIA. The limit of detections (LODs) of AMD and RVB were 1.7 and 1.0 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…According to previous reports, the length of the linker between the hapten and fluorescein would directly affect the sensitivity of FPIA [ 35 , 36 , 37 , 38 , 39 ]. Generally, the linker between the fluorescein and hapten needs to separate the antibody binding site from the fluorescein molecule, so that the antibody can recognize the hapten of tracers through its inherent affinity, with as little steric hindrance as possible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous reports, the length of the linker between the hapten and fluorescein would directly affect the sensitivity of FPIA [ 35 , 36 , 37 , 38 , 39 ]. Generally, the linker between the fluorescein and hapten needs to separate the antibody binding site from the fluorescein molecule, so that the antibody can recognize the hapten of tracers through its inherent affinity, with as little steric hindrance as possible.…”
Section: Resultsmentioning
confidence: 99%
“…Dong et al employed a tracer containing the longest linker to minimize the fluorescence quenching of the fluorescein molecules and to reduce the interference at the antibody binding sites by the fluorescent tags paired with antibodies to develop the best performing FPIA [ 36 ]. There are two studies on the simultaneous detection of analytes using DWFPIA that have been reported [ 25 , 38 ]. However, the effect of linker length on sensitivity was not mentioned or clearly discussed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation